United States digital divide: State level analysis of spatial clustering and multivariate determinants of ICT utilization. (March 2015) - Pick, James B.; Sarkar, Avijit; Johnson, Jeremy
Abstract: This study analyzes factors associated with availability and utilization of information and communication technologies (ICTs) for U.S. states. We construct an exploratory conceptual model of technology utilization in which eight dependent ICT availability and utilization factors are posited to be associated with fourteen independent socio-economic, demographic, innovation, social capital, and societal openness factors. Technology utilization variables are spatially analyzed to determine extent of agglomeration, and regression residuals are examined to eliminate spatial bias. Findings indicate social capital, education, societal openness, urbanization, and ethnicities are significantly associated with ICT utilization. We suggest important implications for policymakers at state and federal levels. Highlights: Digital divide is analyzed for 8 technologies for the states of the U.S. in 2010. Exploratory conceptual model is induced for digital divide of U.S. states. Methods are mapping, cluster analysis, spatial autocorrelation, and regression. Most important ICT correlates are social capital, education, and societal openness. State of Georgia's development of technology exemplifies the model.